Intravenous pamidronate in the treatment of osteoporosis associated with corticosteroid dependent lung disease: an open pilot study. Issue 11 (November 1992) - Gallacher, S J; Fenner, J A; Anderson, K; Bryden, F M; Banham, S W; Logue, F C; Cowan, R A; Boyle, I T
Abstract : BACKGROUND: Bisphosphonates have been shown to be effective agents in the treatment of postmenopausal osteoporosis. Because corticosteroid associated osteoporosis is often associated with increased bone turnover, the effect of intermittent intravenous infusions of pamidronate on this condition has been investigated. METHODS: Seventeen patients (five male) with chronic corticosteroid dependent lung disease (15 asthma, two sarcoidosis) were treated with infusions of 30 mg pamidronate once every three months for one year. These patients had been taking an average of 14 (range 7.5-40) mg prednisolone a day for an average of 14 (range 3-30) years. Bone density measurements, by dual energy x ray absorptiometry, and radiography of the dorsolumbar spine were carried out before and one year after treatment. Bone formation was assessed by measurement of serum alkaline phosphatase and bone resorption by measurement of the fasting urinary hydroxyproline: creatinine ratio at the same time as densitometry and radiography were performed. RESULTS: Pretreatment density of L2-4 and the neck of the femur was significantly lower in these patients compared with a cohort of 100 age and sex matched controls (L2-4 (mean (SEM)): 0.906 (0.050) g/cm2 v 1.142 (0.016) g/cm2; neck of femur: 0.793 (0.030) g/cm2 v 0.936 (0.013)) g/cm2. After treatment there was a significant fall in serum alkaline phosphatase activity from (mean (SEM)) 220 (16) U/1 to 174 (9) U/1 (normal 80-280 U/1) and in the fasting urinary hydroxyproline:creatinine ratio from (mean (SEM) 0.040 (0.006) to 0.024 (0.003) (normal < 0.033). A significant rise was noted in L2-4 density to 0.927 (0.047) g/cm2; mean rise of 3.4%). No change was noted in density of the neck of the femur. CONCLUSIONS: Intermittent infusions of intravenous pamidronate would seem to be effective in both reducing turnover of bone and increasing bone density in corticosteroid induced osteoporosis associated with chronic lung disease. Longer term controlled studies are indicated.